Interaction between MUC1 and STAT1 drives IFITM1 overexpression in aromatase inhibitor-resistant breast cancer cells and mediates estrogen-induced apoptosis - Escher, Taylor E. (Mol Cancer Res, 2019)
The human oncoprotein, mucin 1 (MUC1), drives tumorigenesis in breast carcinomas by promoting epithelial-mesenchymal transition (EMT), epigenetic reprogramming, and evasion of immune response. MUC1 interacts with STAT1, through JAK/STAT signaling, and stimulates transcription of interferon-stimulated genes, specifically interferon-induced transmembrane protein 1 (IFITM1). Our lab has previously shown that IFITM1 overexpression in aromatase inhibitor (AI)-resistant breast cancer cells promotes aggressiveness. Here, we demonstrate that differential regulation of MUC1 in AI-sensitive (MCF-7 and T-47D) compared to AI-resistant (MCF-7:5C) cells is critical in mediating IFITM1 expression. A tumor microarray of 94 estrogen receptor positive human breast tumors correlated co-expression of MUC1 and IFITM1 with poor recurrence-free survival, poor overall survival, and AI-resistance. In this study, we investigated the effects of MUC1/IFITM1 on cell survival and proliferation. We knocked down MUC1 levels with siRNA and pharmacological inhibitors which abrogated IFITM1 mRNA and protein expression and induced cell death in AI-resistant cells. In vivo, estrogen and ruxolitinib significantly reduced tumor size and decreased expression of MUC1, P-STAT1, and IFITM1. Implications: MUC1 and IFITM1 overexpression drives AI-resistance and can be targeted with currently available therapies.